2013
DOI: 10.1126/science.1245622
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Integration of Nuclear ERK Signaling Triggered by Activation of a Few Dendritic Spines

Abstract: The late phase of long-term potentiation (LTP) at glutamatergic synapses, which is thought to underlie long-lasting memory, requires gene transcription in the nucleus. However, the mechanism by which signaling initiated at synapses is transmitted into the nucleus to induce transcription has remained elusive. Here, we found that induction of LTP in only a few dendritic spines was sufficient to activate extracellular signal-related kinase (ERK) in the nucleus and regulate downstream transcription factors. Signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 48 publications
(73 reference statements)
2
117
1
Order By: Relevance
“…Genetically encoded FRET reporters have emerged as useful tools for visualizing dynamic signaling processes in cells with high temporal and spatial resolution. In particular, the Erk activity sensor EKAR (28) and its newer-generation versions (29)(30)(31) have demonstrated robust Erk-activity reporting in a variety of mammalian cell contexts with sensitivity to distinct physiological stimuli (32)(33)(34). Given the close similarity of the enzyme/substrate interaction motifs between Erk1/2 and their MAPK homologs in yeast (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genetically encoded FRET reporters have emerged as useful tools for visualizing dynamic signaling processes in cells with high temporal and spatial resolution. In particular, the Erk activity sensor EKAR (28) and its newer-generation versions (29)(30)(31) have demonstrated robust Erk-activity reporting in a variety of mammalian cell contexts with sensitivity to distinct physiological stimuli (32)(33)(34). Given the close similarity of the enzyme/substrate interaction motifs between Erk1/2 and their MAPK homologs in yeast (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we observe that p90RSK phosphorylation occurred within the nucleus in a time-dependent manner, and at 120 min, it is dependent on afadin nuclear translocation. Interestingly, it has recently been shown that uncaging of glutamate on seven spines is sufficient to increase phospho-ERK1/2 levels in the nucleus of neurons, up to 120 min (20). Critically, p90RSK is directly phosphorylated by ERK1/2 (5); an intriguing possibility is that in the nucleus afadin could function as a scaffold to assemble transcription factors or histone-modifying proteins such as p90RSK, bringing these proteins together as a signaling complex, although future studies will need to test this hypothesis directly.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more prolonged CREB activation (minutes to hours) in response to local LTP induction and restricted Ca 2ϩ influx in dendrites is thought to be mediated by local, postsynaptic CaMKII activation of the ERK pathway followed by slower, longer-distance translocation of ERK signaling from dendrites to nucleus to phosphorylate CREB (87,92,93). In addition, the CREB co-activator CRTC1 is dephosphorylated by CaN in response to LTCC Ca 2ϩ influx triggered by synaptic input to dendrites and then also slowly translocates distally to the nucleus where it is required for CREB-dependent gene expression underlying fear memory (83,94).…”
Section: Coordinated Kinase and Phosphatase Signaling In Postsynapticmentioning
confidence: 99%